“Talleres de danza infantil para desarrollar la psicomotricidad gruesa en los niños de educación inicial" - Millingalle Chancusig, Shirley Geomara (2024)
This research work is based on the need to use dance workshops, as several areas for improvement in the development of the students' gross psychomotor skills are evident. Given this problem, the following objective was set: "to elaborate children's dance workshops to develop gross psychomotor skills in the children of the "Victoria Vásconez Cuvi" Educational Unit in Early Education. For the development of this research, the non-experimental qualitative methodology was applied, using the inductive method, jointly applying instruments such as a guide of structured questions and the observation sheet, working with a population of 35 children and a teacher. It was possible to determine the children's need for training, which was detrimental to gross motor development due to the lack of implementation of new teaching-learning strategies. Therefore, a proposal for dance workshops to develop gross motor skills in early childhood education children was developed and validated by two experts and two users who agreed that including dance as a strategy would be effective in improving the development of motor skills involving the strengthening of laterality, balance, coordination, and body awareness.